CHANGE MANAGEMENT OF TAHFIDZ KHAIRUNNAS SRESEH SAMPANG ISLAMIC BOARDING SCHOOL AS A STRATEGIC EFFORT TO DEVELOP INSTITUTIONAL QUALITY - Soleh, Badrus; Wahyudi, Kacung; Buna'i; Karofis, Shofiatul; Masrurah , Waqiatul (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2024)
This research aims to describe the change management of the Tahfidz Khairunnas Sreseh Sampang Islamic Boarding School which includes planning, implementation and control systems. This research uses a qualitative approach with a case study type. Data sources were obtained through interviews, observation and documentation. Informants include the Islamic boarding school manager, dormitory head/caretaker, and mudabbir. Meanwhile, data analysis is carried out through condensation, presentation and conclusions. The results of this research show that the planning for changes to the Tahfidz Khairunnas Islamic boarding school includes planning for takhassus and non-takhassus programs, student targets that are clearly arranged in the Sikhair application system, financing with two types, namely regular and scholarships, sophisticated teaching and learning facilities such as tablets and projectors, a clear vision and mission. created from the center, as well as gel system planning. The implementation of changes in Islamic boarding schools includes the implementation of the vision and mission carried out with collaboration (internal and external), the use of the tasmi', ziyadah and murojaah curriculum, and the application of the cultures found in Islamic boarding schools. Meanwhile, controlling changes in Islamic boarding schools is by implementing the Trello application as a performance control system, implementing the Sikhair application, and holding regular ten-minute meetings every day.